Projected number of people in need for long-term care in Germany until 2050 - Haß, Luisa; Knippschild, Stephanie; Tönnies, Thaddäus; Hoyer, Annika; Palm, Rebecca; Voß, Sabrina; Brinks, Ralph (Frontiers in Public Health, 2024)
Introduction: Current demographic trends predict continuously growing numbers of individuals reliant on care, which has to be accounted for in future planning of long-term careresources. The projection of developments becomes especially necessary in order to enable healthcare systems to cope with this future burden and to implement suitable strategies to deal with the demand of long-term care. This study aimed to project the prevalence of long-term care and the number of care-dependent people in Germany until 2050.Methods: We used the illness-death model to project the future prevalence of long-term care in Germany until 2050 considering eight different scenarios. Therefore, transition rates (incidence rate and mortality rates) describing the illness-death model are needed, which have been studied recently. Absolute numbers of people in need for long-term care were calculated based to the 15th population projection of the Federal Statistical Office.Results: Numbers of people in need for long-term care will increase by at least 12%, namely 5.6 million people, in the period of 2021 until 2050. Assuming an annual incidence-increase of 2% from 2021 to 2050 the number of care-dependent individuals could potentially rise up to 14 million (+180%).Conclusions: Our projections indicated a substantial rise in the number of care-dependent individuals. This is expected to lead to raising economic challenges as well as a stronger demand for healthcare and nursing personnel.